ANALISIS IMPLEMENTASI PENDEKATAN SAINTIFIK PADA PROGRAM UNGGULAN SEKOLAH DASAR ALAM RUMBAI PEKANBARU - Esi Rahmadani; M. Jaya Adiputra; Lazim. N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The Indonesian curriculum strongly underlines the student-centered scientific approach. Every public and private school has applied learning with a scientific approach. But there is one school that is different from the school in general, namely schools that use the concept of nature as a source of learning. This school has a superior program that distinguishes it from other schools. Qualitative descriptiveresearch aims to determine the implementation of the scientific approach to nature education using data acquisition techniques through observation, interviewing and documentation using data analysis techniques that collect and subsequently reduce data, present data and finally draw conclusions. Five steps in the scientific approach of observing, questioning, trying, thinking and communicating have been carried out in 14 excellent programs. This research is useful to give special researchers insight intonature schools and to motivate teachers to better apply the scientific approach for the next ones.Key Words: Scientific Approach, Nature School